Expression and functional study of DNA polymerases from Psychrobacillus sp. BL-248-WT-3 and FJAT-21963 - Sun, Yaping; Ko, Danny Hsu; Gao, Jie; Fu, Kang; Mao, Yuanchen; He, Yun; Tian, Hui (Frontiers in Microbiology, 2024)
The properties of DNA polymerases isolated from thermophilic and mesophilic microorganisms, such as the thermophilic Geobacillus stearothermophilus (Bst) and mesophilic Bacillus subtilis phage (Phi29), have been widely researched. However, DNA polymerases in psychrophilic microorganisms remain poorly understood. In this study, we present for the first time the expression and functional characterization of DNA polymerases PWT-WT and FWT-WT from Psychrobacillus sp. BL-248-WT-3 and FJAT-21963. Enzymatic activity assays revealed that FWT-WT possessed strand displacement but lacked exonuclease activity and high ionic strength tolerance, whereas PWT-WT lacked all these properties. Further protein engineering and biochemical analysis identified D423 and S490 as critical mutation sites for improving strand displacement and tolerance to high ionic strength, specifically in the presence of 0–0.3 M potassium chloride (KCl), sodium chloride (NaCl), and potassium acetate (KAc). Three-dimensional structural analysis demonstrated that the size and the electric charge of the single-stranded DNA (ssDNA) encapsulation entrance were pivotal factors in the binding of the ssDNA template.